Spatial and Temporal Variation of Precipitation Extreme in the Kathmandu Valley During Last Three Decades - Khanal, Kripa; Baniya, Binod; Sigdel, Madan; Khadka, Jyoti; Dhital, Yam Prasad (Journal of Hydrology and Meteorology, 2024)
Changes in the severity, duration, and frequency of various meteorological fundamentals are thought to be the primary source of the world’s changing climate. Precipitation extremes are one of significant events triggered by changes in the climate system. The Mann-Kendall Trend test was used to analyze the precipitation trend, and ClimPACT2, an R software package, was used to calculate sector specific climate indices for the daily precipitation data from 1990 to 2022. The data set used in this study included daily precipitation data from 5 weather stations in the Kathmandu valley. The result showed that monsoon precipitation contributing to 70-80% of average annual rainfall in which the monsoon precipitation was found the highest in Godawari and lowest in Khumaltar. The annual rainfall variability in the valley found to be 847-2367 mm. Godavari and Bhaktapur has decreased rainfall at the rate of -12.59 mm and 4.57 mmyr-1respectively. The Kathmandu airport, Khumaltar and Panipokhari shows an increasing trend with average annual rainfallincreasing by 4.45 mmyr-1, 1.95 mmyr-1and 2.63 mmyr-1, respectively during 1990-2022. The average monthly precipitation in the Kathmandu Valley ranged from 4.09 to 454.29 mm received maximum rainfall by the Godavari. Spatially, the maximum rainfall reached to 1971 mm during monsoon especially in the Godawari and Panipokhari area. The heavy precipitation days (R10 mm) and very heavy precipitation days (R20mm) was higher in Godawari (70 days) and Panipokhari (42 days) and lowest in Khumaltar (9 days). In Panipokhari, the maximum lengths of consecutive wet and dry days were observed over 32 days and 202 days respectively. The highest annual maximum values of 1-day and 5-day precipitation amount within a year was highest in Godawari in the range of 52 to 225 mm, and 121 to 476 mm and the annual total precipitation over the certain long-term 95th & 99th percentile was also highest for Godawari station. These varied results in the range, duration, and frequency of precipitation patterns could be due to the changing climate.